Вплив пружного закріплення лопатей на динаміку вітроколеса - Корендій, Віталій (Видавництво Львівської політехніки, 2011)
З метою встановлення впливу параметрів жорсткості лопатей на їх динамічну поведінку при складному обертанні вітроколеса поставлено задачу про коливання жорсткої лопаті, пружно приєднаної одним кінцем до жорсткого диска, що зв’язаний з жорстким валом. Для побудови нелінійних рівнянь руху пружно закріпленої жорсткої лопаті при складному обертанні вітроколеса застосовано теорему Коріоліса та принцип Даламбера. Отримано частинний розв’язок рівнянь руху, що описує режим сталих коливань жорсткої лопаті. Встановлено, що система має малу структурну жорсткість, а резонансні режими у ній не виникають. The solution of the actual problem that consists in investigation of typical vibration processes in compound rotation of rigid blades, elastically attached to the wind wheel, is given in this article. With the aim to establish the influence of stiffness parameters of rigid blades on their dynamic behavior in compound rotation of the wind wheel, the problem about vibrations of rigid blades, attached by one end to the rigid disc connected with a rigid shaft, is set up. The theorem of Coriolis and the principle of Dalamber are used for construction nonlinear equations of motion of rigid blade in compound rotation of the wind wheel. Analytical expressions for calculation the vectors of transposed (2), comparative (5), coriolis (6) and full (1) acceleration of the element of the blade are deduced. These expressions enable us to compute the components of inertial loads on the element of the blade, which are caused by rotation of the shaft of the wind wheel. We eliminate the system of nonlinear equations (7) of motion of rigid blade to one linear differential equation of vibration (8) using some assumptions described in the article. The partial solution (9) of received equation that describes behavior of constant vibrations of rigid blade is found. Mathematical and computer modeling of dynamics of described system is realized. We take into consideration the possibility of variation of some typical parameters, such as angular velocity of rotation or turning of the wind wheel, number of blades, geometric dimensions and density parameters of the blade etc. Some graphical results of computer modeling (graphics of the oscillation amplitude) are given in the article. We prove that resonance processes on the elementary areas of blades in case of compound rotation of the wind wheel with rigid blades elastically attached to the rotor don’t take place and the system has small structural stiffness.
The influence of elastic attachment of the blades on dynamics of the wind wheel
Keywords: коливання; жорсткі лопаті; вітроколесо; складне обертання; сили інерції; резонансні режими